PEMAHAMAN MEMBACA NASKAH BERITA DENGAN MENGGUNAKAN METODE KOOPERATIF STAAD PADA MATA PELAJARAN BAHASA INDONESIA - Astuti, Puji (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2019)
ABSTRACTThe choice of the problem of classroom action research is based on the fact that students' ability to read news texts is still very low. Whereas with the mastery of Indonesian language lessons in general students do not have difficulty learning other subjects. This research was conducted in July to November 2015, because in those months the students had completed the first semester of the general exam and were still at the beginning of the second semester so that the students' conditions could be observed from the beginning.Cooperative Method STAD is a learning method wherein the learning process teaches the teacher to invite students to work together in groups to complete assignments in the classroom and allow students to find information on information that can be traditionally told or disguised.From this writing it can be concluded that with the motivation in learning STAD cooperative learning methods the students' ability to read news scripts increases and learning outcomes will be optimal. The more precise the motivation given, the more successful the lesson will be. With high motivation, the intensity of student learning efforts will also be high. So motivation will always determine the intensity of student learning. This will improve student understanding.Keywords: Reading News Scripts, Cooperative STAD